Impact of Financial Development and Economic Growth on Energy Consumption in Developing Countries of Asia - Usman, Muhammad; Rasheed, Kiran; Mahmood, Faiq; Riaz, Ahsan; Bashir, Mohsin (International Journal of Energy Economics and Policy, 2023)
This study investigates the impact of financial development and economic growth on energy consumption by controlling variables such as urbanization and globalization in developing countries of Asia for the era of 1991-2019. Data related to financial development, economic growth, energy consumption and urbanization is collected from World Development Indicator and data related to globalization is collected from Konjunkturforschungsstelle (KOF) index of globalization. In this research Dynamic seemingly unrelated regression model is applied to test the hypothesis. According to the outcomes of DSUR the impact of financial development on energy consumption is positively substantial as increase of 1 unit in financial development brings 3.07% rise in energy consumption, the effect of GDP on energy consumption is positively influential as increase of 1 unit in GDP brings 0.29% increase in energy consumption and the influence of globalization is unfavorable but substantial as increase of 1 unit in globalization brings decrease of 15.57% in energy consumption. Moreover, the influence of urbanization on energy consumption is positive and considerable, as increase of 1 unit in urbanization brings 11.54% increase in energy consumption. Moreover, there is two way connections among GDP and financial development. Moreover, Asian countries should adopt energy conservation policies.